Realisasi Prinsip Kerja Sama Dan Potensi Pendidikan Karakter Dalam Wacana "Indonesia Lawak Klub" Trans 7 Sebagai Bahan Ajar Bahasa Indonesia Di SMA/K - Rahayu, Puji, Prof. Dr. Harun Joko Prayitno, M.Hum (2016)
This study has three goals to be achieved, (1) describe maxims of the principle of cooperation contained in the discourse "Indonesia Lawak Klub " in trans 7 (2) describe the values of potential character education in the discourse "Indonesia Lawak Klub", (3) describe the use of maxims principles of cooperation as teaching materials "Bahasa Indonesia" at SMA/SMK. This research uses descriptive method qualitative which approachment of qualitative research strategy using content analysis. The methods and techniques used in this research is data collection and note methods. Methods of data analysis used equivalent methods, equivalent method used is equivalent method that pragmatic people who become dialogue partner. Next method used intralingual and method used ekstralingual. The results of this study show that in the discourse "Indonesia Lawak Klub" in trans 7 there are four maxims of the cooperative principle, they are, maxim of quantity, maxim of quality, the maxim of relevance, maxim implementation. ILK's even not only produce maxims principle cooperation alone, but also be able to show the potential of character education. Found seven charakter education namely, toleransi, independent, democratic, curiosity, the spirit of nationalism, patriotism, and caring environment. There are four maxims principles of cooperation in the above that can be used as teaching materials "Bahasa Indonesia" at SMA/SMK, quantity, quality, relevance, and execution. Basic Competency used is 32.2.7 implementing a shift in communication.